Control as a Service: A Microservice Approach to Industry 4.0 - Bigheti, Jeferson A.; Fernandes, Michel M. [UNESP]; Godoy, Eduar Do P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The Industry 4.0 (I4.0) is a new concept of production that requires a jointly use of industrial automation and information technologies in order to obtain greater efficiency, quality and productivity. The I4.0 implementation is tied to the application of recent technologies such as the Industrial Internet of Things and Cloud Computing. In this context, the paradigm of collaborative automation through the use and sharing of services provides a flexible, distributed and integrated architecture using communication networks. This paper focuses on the proposal of a microservice oriented architecture (MOA) for I4.0 applications. A review about industrial service-oriented architecture (SOA) applications and composition of services are presented. The development of microservices for the MOA architecture is presented as well as a case study of a closed process control loop as service.
Keywords: Industrial Internet of Things; Moleculer framework; Process control; Service oriented architecture